Extended Abstracts of Contributions to the PhD Conference of Members to the Alps-Adriatic Rectors’ Conference: Contributions to the Topics of Quality of Life for Youth and Circular Economy in the Alps-Adriatic Region in the Year of the Presidency of Slovenia Over the European Union Strategy for the Alpine Region (University of Maribor Press, 2025)
University of Maribor hosted this year’s AARC PhD Conference titled “Thinking of the Quality of Life for the Young Generation in the Alpine and Adriatic Region through the Eyes of a Young Researcher in Circular Economy and Human and Social science”. PhD students of Alps-Adriatic Rectors’ Conference and Danube Rectors’ Conference member universities and DRC member universities from Albania, Austria, Germany, Hungary, India, Myanmar, Serbia, Slovakia, Slovenia and Ukraine presented their doctoral studies and research related to the conference topic. The introductory note was given by Prof. Dr. László Komlósi from Széchenyi István University on the elements of a successful PhD study. Background of the conference topic are two annual priorities of the Presidency of Slovenia over the European Union Strategy for the Alpine Region (EUSALP), namely the circular economy and the quality of life of the youth in the Alpine region. The participants had an opportunity to compare their understanding of their mission as future creators of the destiny of the area that they live in with other opinions and thoughts of colleagues from different countries and scientific fields.